Directed Self‐Assembly of Patchy Microgels into Anisotropic Nanostructures. Issue 2 (3rd December 2019) - Xu, Jianchang; Wang, Zhikun; Zhang, Fusheng; Peng, Shiyuan; Zhang, Jing; Zhang, Lijuan
Abstract: Multi‐geometry nanostructures with high‐order, complex, and controllable geometries have attracted extensive attention in the development of functional nanomaterials. A simple and versatile strategy is proposed to construct various anisotropic nanostructures through the directed self‐assembly (DSA) of patchy microgels. A general criterion for interaction parameters is developed by the variance analysis method to achieve the formation of 1D nanorods by the single directional DSA process, and 2D or 3D polymorphs including V/T/h/cross shapes, multiple arms, multi‐directional bending, single/multiple rings, nanocages, etc., by the multi‐directional DSA process of binary microgel blends. At the optimum interaction parameters, the nanorods exhibit the quickest formation process and the most thermodynamically stable geometry, while the various 2D or 3D assemblies exhibit controlled jointing behaviors for versatile assembly geometries. The number of recognition sites on the patchy microgel surface guides the aggregation modes of microgels during the DSA process. These assemblies can bear large curvature variance with the increase of shear rates due to the high flexibility and the ability of adjusting orientation spontaneously. The DSA behavior of patchy microgels differs from the traditional self‐assembly process of block copolymers, which may open a new route for guiding the formation of controllable nanoparticle architectures. Abstract : A simple and versatile strategy is proposed to construct various anisotropic nanostructures through the directed self‐assembly (DSA) of patchy microgels. A general criterion of interaction parameters is developed to achieve the formation of 1D nanorods by the single directional DSA process. Inspired by architectural technology "butt joint, " binary microgel blends could cooperatively self‐assemble into 2D or 3D anisotropic nanostructures.